Is Low Hemoglobin Level a Risk Factor for Acute Lower Respiratory Tract Infections? - Malla, Tejesh; Pathak, Om K; Malla, Kalpana K (Journal of Nepal Paediatric Society, 2009)
Objective: This prospective study was conducted to evaluate whether a low hemoglobin level, was a risk factor for Acute Lower Respiratory Tract Infections (ALRTI) in children. Methods: 150 Children of all age groups who came to the outpatient department and those admitted for ALRTI were included in the study. Age and sex-matched 140 children, not having any respiratory illness, were taken as control. The study period was from March 2006 - March 2007. Detailed clinical and laboratory evaluation of the enlisted patients was done. All were subjected to detail investigations. Results: Radiological evidence of pneumonia was present in 70 (50 %) children.Hyperinflated lungs were seen in 40 (29%) and was normal in 30 (21.4%) cases. Blood culture was positive in 14 (10%) children of study group and none among control group. Klebsiella was the commonest organism isolated 6 (4.2%) in blood culture positive cases. The mean Hemoglobin (Hb) level of study group was 9.88 gm% and it was 12 gm% in control group.96 (68.6%) of study group and 30 (21.42%) of control group had anemia. Of the anemic children, 79 (82.3%) in study group had iron deficiency, and 17 (17.7%) had normocytic normochromic anemia. These values were 18 (33.3%) and 36 (66.6%) respectively for control group. Low hemoglobin level was a risk factor (p<0.001) ALRTI. Conclusion: Anemic children were 3.2 times more susceptible to ALRTI compared to the control group and and iron deficiency anemia was predominating. Supplemental iron therapy may reduce the incidence of ALRTI. Prevention of anemia, due to whatever etiology is also essential. Key words: ALRTI, anemia, hemoglobin. DOI: 10.3126/jnps.v30i1.2453 Journal of Nepal Paediatric Society Vol.30(1) 2010 1-7